A general outlook as to the participation of general hospital's regarding attention to patients with Hansen's disease - Guimarães, Cid (Revista de Saúde Pública, 1975)
A historical synthesis shows that the hospital has turned its attention towards the curative aspects of medicine. Diagnosis and therapeutic progress have much contributed towards this, in especial. The lazarets and their later version, the isolation hospitals, have helped in maintaining the general hospitals away, until very recently, from Hansen's disease. The medical school hospitals of São Paulo are exceptions. The importance of the education of the medical and administrative staff, the patients of the hospital, as well as the general public is stressed as being the only way of integrating assistance to the bearers of Hansen's disease in the general hospitals within a short period. A systematic approach is proposed as the solution, as Hansen's disease ought to be considered as a normal component of the general health programme. The advantages of including the patient with Hansen's disease in the general hospital's clientele in order to treat him as any other are also pointed out.